Effects of maternal healthcare service utilization on modern postpartum family planning access in Bangladesh: insights from a National representative survey. - Md Nuruzzaman Khan; Md Mostaured Ali Khan; Md Arif Billah; Shimlin Jahan Khanam; Md Moinuddin Haider; Bidhan Krishna Sarker; Melissa L Harris (PLoS ONE)
Background Access to modern family planning is critical for improving maternal and child health outcomes, yet it remains severely lacking in low- and middle-income countries, including Bangladesh. Maternal healthcare utilization during and after pregnancy is vital for promoting postpartum family planning. This study examined the effects of maternal healthcare service utilization on postpartum family planning uptake in Bangladesh. Methods Reproductive calendar data from 4,081 women with recent live births were extracted from the cross-sectional 2017/18 Bangladesh Demographic and Health Survey and analyzed. The outcome variable was uptake of modern postpartum family planning methods and the exposure variables were different types of maternal healthcare services. Kaplan-Meier methods were used to calculate cumulative probabilities of modern postpartum family planning method uptake within 12 months post-delivery, and modified Poisson regression models were used to estimate the effects of utilizing maternal healthcare services on modern postpartum family planning method uptake. Results Modern family planning methods in the 12 month postpartum period were used by 72% of women, with over 60% starting after day 40. Less than 4% used long-acting family planning methods, while almost 40% relied on the oral contraceptive pill. Utilizing maternal healthcare services was associated with up to a 7% higher uptake of modern postpartum family planning methods compared to non-users. Conclusion Three-quarters of Bangladeshi women use modern family planning within the 12 months postpartum, but often rely on less effective methods. Additionally, 25% of these women resort to traditional or no use of contraceptive methods, increasing the risks of unintended pregnancy, short birth intervals, and adverse maternal and infant health outcomes. Maternal healthcare services, including private facilities, should prioritize modern postpartum family planning provision, along with education and counseling on the benefits of long-acting contraception.